A Direct Interaction between Causative Genes of DYT1 and DYT6 Primary Dystonia - Gavarini, Sophie (2010)
Primary dystonia is a movement disorder characterized by sustained muscle contractions and in which dystonia is the only or predominant clinical feature. TOR1A (DYT1) and the transcription factor THAP1 (DYT6) are the only genes identified thus far for primary dystonia. Using electromobility shift assays and chromatin immunoprecipitation (ChIP)-qPCR, we demonstrate a physical interaction between THAP1 and the TOR1A promoter that is abolished by pathophysiologic mutations. Our findings provide the first evidence that causative genes for primary dystonia intersect in a common pathway and raise the possibility of developing novel therapies targeting this pathway.